2015
DOI: 10.1007/s11999-015-4507-3
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of Comorbidities on Self-rated Hand Function in Patients With Symptomatic Trapeziometacarpal Arthritis?

Abstract: Background The thumb trapeziometacarpal joint is one of the most common sites of arthritic degeneration prompting specialty care. Surgical treatment algorithms are based on radiographic arthritic progression. However, the pain and disability attributable to trapeziometacarpal arthritis do not correlate with arthritic stage, and depression has independently predicted poorer self-rated hand function both at baseline and after treatment in patients' atraumatic hand conditions. Questions/purposes (1) Does thumb tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
(38 reference statements)
3
18
0
4
Order By: Relevance
“…Affected patients experience similar absolute improvements in function after treatment but remain at lower levels of function overall, starting and finishing at a lower level than unaffected patients 24 . In our sample of rLRTI patients, we cannot definitely determine the impact of the comorbidity of depression 23,24 . We hypothesize that it may have impacted our data in two ways.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Affected patients experience similar absolute improvements in function after treatment but remain at lower levels of function overall, starting and finishing at a lower level than unaffected patients 24 . In our sample of rLRTI patients, we cannot definitely determine the impact of the comorbidity of depression 23,24 . We hypothesize that it may have impacted our data in two ways.…”
Section: Discussionmentioning
confidence: 94%
“…This finding was exploratory as this study was not designed to evaluate the impact of depression on LRTI outcomes. A history of depression has been documented to result in poorer self-reported hand function in patients with TMC arthritis 23 . Depressive symptoms have also impacted patients’ self-reported hand function after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…or other upper-extremity comorbidities [16,17]. To reduce the uncertainty due to individual variance, we made paired analyses of the individual improvement in PROM.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review from 2017, 3 of 5 studies showed a significant correlation between patient satisfaction and psychological measures of depression and mental health in CTS patients [16]. Studies further show that selfreported depression is correlated to poorer self-evaluated hand function in patients suffering from trapeziometacarpal arthritis [17]. In CTS patients, preoperative hospital anxiety is associated with worse preoperative symptom severity [18].…”
Section: Introductionmentioning
confidence: 99%